Burkholderia mallei and Burkholderia pseudomallei stimulate differential inflammatory responses from human alveolar type II cells (ATII) and macrophages - Lu, Richard; Popov, Vsevolod; Patel, Jignesh; Eaves-Pyles, Tonyia (Frontiers in Cellular and Infection Microbiology, 2012)
Alveolar type II pneumocytes (ATII) and alveolar macrophages (AM) play a crucial role in the lung’s innate immune response. Burkholderia pseudomallei (BP) and Burkholderia mallei (BM) are facultative Gram-negative bacilli that cause melioidosis and glanders, respectively. The inhalation of these pathogens can cause lethal disease and death in humans. We sought to compare the pathogenesis of and host responses to BP and BM through contact with human primary ATII cells and monocytes-derived macrophages (MDM). We hypothesized that because BP and BM induce different disease outcomes, each pathogen would induce distinct, unique host immune responses from resident pulmonary cells. Our findings showed that BP adhered readily to ATII cells compared to BM. BP, but not BM, was rapidly internalized by macrophages where it replicated to high numbers. Further, BP induced significantly higher levels of pro-inflammatory cytokine secretion from ATII cells (IL-6, IL-8) and macrophages (IL-6, TNFα) at 6h post-infection compared to BM (p<0.05). Interestingly, BM induced the anti-inflammatory cytokine, IL-10, in ATII cells and macrophages at 6h post-infection, with delayed induction of inflammatory cytokines at 24h post-infection. Because BP is flagellated and produces LPS, we confirmed that it stimulated both Toll-like receptor (TLR) 4 and TLR5 via NF-κb activation while the non-flagellated BM stimulated only TLR4. These data show the differences in BP and BM pathogenicity in the lung when infecting human ATII cells and macrophages and demonstrate the ability of these pathogens to elicit distinct immune responses from resident lung cells which may open new targets for therapeutic intervention to fight against these pathogens.